Slotted circular patch UWB monopole antenna with notch-band characteristics / Hanisah Mohd Zali - Mohd Zali, Hanisah (2012)
This paper reports on the design of a UWB Planar Monopole Antenna with band notch characteristic at 5-6 Ghz frequency band to reduce inter-system interference with Wireless Local Area Network (WLAN) system. The antenna configuration is based on a pair of thin slots on the circular patch with the step on its feeding line and half ground plane. Antenna is fabricated on FR-4 substrate having Er= 4.3, h= 1.5 mm (thickness). The fabricated antenna yielded VSWR value lower than 2 from 3 to IO Ghz frequency band, excluding the 5-6 Ghz region. The radiation properties of the antenna are also investigated throughout the UWB frequency band.